2020
DOI: 10.1155/2020/6457982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Four Grape Varieties on the Physicochemical and Sensory Properties of Unripe Grape Verjuice

Abstract: Verjuice is a sour-tasting juice obtained from the mechanical pressing of unripe grapes. The significance of verjuice as food product includes but not limited to its richness in antioxidant compounds, its usage as an alternative to lemon and vinegar, and also its production which can reduce the losses of lower quality grapes and waste from grape thinning. In this study, a survey for the common Lebanese traditional preparation methods for verjuice was done and physicochemical properties of four Lebanese verjuic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The same authors found that the harvest date (three different dates) had no influence on the aromas whereas it did have an effect on taste, while the opposite results were found according to preservatives (sulfite or sorbate). It has also been shown that the use of different grape cultivars in verjuice production affects both the physicochemical and sensory properties, with some cultivars being more suitable to obtain a juice with higher concentration of antioxidant compounds and a more appreciable colour (Salah Eddine et al 2020).…”
Section: Properties Of Ugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors found that the harvest date (three different dates) had no influence on the aromas whereas it did have an effect on taste, while the opposite results were found according to preservatives (sulfite or sorbate). It has also been shown that the use of different grape cultivars in verjuice production affects both the physicochemical and sensory properties, with some cultivars being more suitable to obtain a juice with higher concentration of antioxidant compounds and a more appreciable colour (Salah Eddine et al 2020).…”
Section: Properties Of Ugsmentioning
confidence: 99%
“…In this context, previous studies conducted on red wine suggested that monomeric flavon‐3‐ols, procyanidin dimers and trimers are partly responsible for bitter taste and the perception of astringency (Peleg et al 1999). Moreover, several reports have indicated that verjuice is characterised by a sour taste, since it is obtained from grapes that are harvested approximately 45 days after flowering, thus it displays a high amount of organic acids and a low sugar concentration (Nikfardjam 2008, Hayoglu et al 2009, Salah Eddine et al 2020). These data were also confirmed in a recent study where phenol‐rich extracts obtained from UGs dissolved in water solutions were subjected to sensory descriptive analyses (Bucalossi et al 2020).…”
Section: Properties Of Ugsmentioning
confidence: 99%
“…An alternative use of unripe grapes is the production of verjuice, an acidic juice traditionally produced in the Mediterranean area, which is extracted from the mechanical pressing of unripe green grapes. Verjuice has been mainly studied for its physicochemical and sensory properties [ 21 , 22 ], while its bioactive compounds were just recently isolated [ 23 , 24 ]. In grape berries, HCAs are constituted by caffeic, coumaric, and ferulic acids and are present mainly in their ester forms, associated with tartaric acid giving caftaric (CFA), coutaric (CUA), and fertaric (FEA) acids, respectively [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the compounds are further concentrated by crystallization upon acidification of the extract and its cooling or by evaporation at high temperatures (about 90 °C) that could, however, degrade HCAs. This last concentration step permits the achievement of purity values above 90% w/w [ 21 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation